Impact of increasing local economic capacity on reducing maritime logistics costs in island Province of eastern Indonesia: A dynamic system approach - Chairullah Amin; Abdul Wahab Hasyim; Muammil Sun'an; Yetty; Rafiazka Millanida Hilman; Hafida Fahmiasari (Transportation Research Interdisciplinary Perspectives)
The archipelagic state of Indonesia requires an efficiently integrated maritime logistics system. Integrating the maritime logistics system results in advantages for remote and difficult-to-reach areas, especially in the islands, to improve supply chain efficiency for the basic needs of island communities. The study explored how increasing economic activity in islands can enlarge the throughput volume and decrease maritime logistics costs. The method used the dynamic system to investigate the relationship between the sub-systems of regional economics, port throughput, and maritime logistics costs. The result suggested that an economic growth rise of 7,5% influenced the increasing cargo throughput by 2% and decreased sea transportation costs by 0,0059%. Developing logistics centers near islands may lower ship operational costs and effectively solve the inefficiency of maritime logistics costs in the eastern part of Indonesia.